Hegemoni Meja Makan: Membentuk Pragmatisme Pemahaman pada Masyarakat melalui Makanan - Afina Rahma Hadiyati; Agus Afandi (LPPM Universitas Negeri Surabaya, 2024)
Globalization has become an arena for ideological battles between the ruling class and people who do not have power will be hegemonized by the ideology of the ruling class. Globalization becomes an arena for transformation in culture, including in consuming food. Hegemony can also enter the family dining table space in understanding pragmatism in determining food menu decisions that have an impact on society, especially the people of North Kemodo Hamlet. This research offers insight into the dining table can shape behavior and society towards understanding food. This research offers insight into how decisions to consume food in people's daily lives can shape people's behavior and understanding of food, and reveals how the ruling ideology affects food habits and food choices in everyday life. Keywords: Globalization; Pragmatism; hegemony; and Food.